2020
DOI: 10.3389/fimmu.2020.00288
|View full text |Cite
|
Sign up to set email alerts
|

Mass Cytometry Studies of Patients With Autoimmune Endocrine Diseases Reveal Distinct Disease-Specific Alterations in Immune Cell Subsets

Abstract: Although there is evidence that autoimmune diseases share similar immunogenetic mechanisms, studies comparing peripheral CD45 + cells from patients with autoimmune endocrine diseases in parallel are limited. In this study, we applied high-dimensional single-cell mass cytometry to phenotypically characterize PBMC from patients with new-onset (N-T1D) and long-standing type 1 diabetes, Hashimoto's thyroiditis (HT), Graves' disease and autoimmune Addison's disease (AD), as well as healthy controls. The frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…However, the efficacy of L-T4 supplementation among euthyroid women applied to prevent miscarriage and preterm birth induced by HT in recent research is inconsistent ( Figure 1 B ). Notably, with the extended exploration of HT in recent years, an abnormally activated proinflammatory state of the immune system is found in these patients 14 , 17 , 18 , 33 - 35 . Therefore, these findings enrich our knowledge of HT-related miscarriage, especially in euthyroid women.…”
Section: Ht and Miscarriagementioning
confidence: 99%
See 2 more Smart Citations
“…However, the efficacy of L-T4 supplementation among euthyroid women applied to prevent miscarriage and preterm birth induced by HT in recent research is inconsistent ( Figure 1 B ). Notably, with the extended exploration of HT in recent years, an abnormally activated proinflammatory state of the immune system is found in these patients 14 , 17 , 18 , 33 - 35 . Therefore, these findings enrich our knowledge of HT-related miscarriage, especially in euthyroid women.…”
Section: Ht and Miscarriagementioning
confidence: 99%
“…Although HT is regarded as one of organspecific autoimmune diseases (ADs), numerous clinical studies have confirmed that similar to other ADs, HT plays a vital role in women's miscarriage and even RM [9][10][11][12][13]. With the development of cellular and molecular immunology, accumulating studies have found that not only hypothyroidism but also immune system disorders [14] caused by HT conditions are involved in the pathogenesis of…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the power of mass cytometry has recently been applied to dissect immune dysfunction in a pilot study including patients with different endocrine autoimmune disorders. 58 Diverging immunological mechanisms in a single autoimmune disease is common and needs to be characterized precisely for better understanding of disease pathogenesis. Recent studies have used CyTOF to characterize the immune system in autoimmune T1D, 59 SLE 60 and RA, 61,62 but very few studies have focused on autoimmune endocrine diseases.…”
Section: Mass Cytometry/cytofmentioning
confidence: 99%
“…Viral infections have indeed been suggested to take part in the pathogenesis of autoimmune disease, 14 highlighting the importance of studying early changes during viral infections. Furthermore, the power of mass cytometry has recently been applied to dissect immune dysfunction in a pilot study including patients with different endocrine autoimmune disorders 58 . Diverging immunological mechanisms in a single autoimmune disease is common and needs to be characterized precisely for better understanding of disease pathogenesis.…”
Section: Single‐cell Technologiesmentioning
confidence: 99%